Implementasi Metode Tarjih dalam Menyikapi Hadis-hadis Kontradiktif - Zahrotun, Zahrotun (Institut Agama Islam Sumatera Barat, 2024)
In this development, the scholars found several indications of the hadith of the Prophet that seemed to contradict each other or there was an altercation between one hadith and another, this then made it difficult to make it a hujjah, as a result the scholars formulated the idea of ??solving these hadiths which have the potential to contradict each other. arud (preventing or hindering), this settlement is carried out using various methods, in this case the last way to complete the Ikhtilaf is the tarjih method. Departing from the background of these problems, specifically, this research wants to ask two questions 1) what are the rules for memorizing hadith. 2) what are examples of the implications of the tarjih method in hadiths which are still considered contradictory. To answer these two questions, the author uses the library method to collect data related to this research. The results of this study are the principles in memorizing hadith which contradict the 7 rules that must be fulfilled, namely tracing the condition of the narrator, the age of the narrator, the procedure for narration, the time of narration, the editorial of the hadith, the legal content, and external elements